Studi Pengembangan Model Turbulen Îº-Îµ untuk Sirkulasi Arus I: Aliran Dua Dimensi pada Sebuah Tampungan Air - M. Syahril Badri Kusuma; M. Cahyono; Eka Oktarianto (Journal of Mathematical and Fundamental Sciences, 2004)
This paper present the results of the Îº-Îµ model development for simulating two dimensions flow in a small reservoir. The study was aimed to see wether the turbulent component could be better accounted by using the Îº- Îµ model. The numerical model was developed using finite difference method where hydrodynamic equation was solved by the combination of Mc Cormack and splitting methods. The mirror method is used as the boundary condition of the model.Comparison study were done by using the field measurement result on fishery ponds and model results by other methods. Better agreement is found between field measuremenst and model results due to the increasing accuracy in turbulent model prediction.